The Principle of the Endowment Stated in the Text of Law According to the Decisions of the Court of Cassation - Ali Shakir Mahmood Mohamed; Sabir Hussien Eliwy Muhammed (Genius Journals, 2023)
Endowment (Waqf) has a great importance in public life, and thus it receives special attention and care from researchers, as it is not just a social and moral system that achieves benefits for its parties, whether they are the endower or the beneficiaries, but it extends to the society by achieving the element of social solidarity and providing employment opportunities and financial resources for sectors of the society. Additionally, endowment has a religious aspect related to the endower's connection to Allah Almighty, as some scholars have stipulated the proximity to Allah Almighty for the validity of endowment. Thus, endowment has reached the level of sanctity, making it perpetual and making it an independent person from the owner (endower) of the property. This relieves the endower from financial obligations, but this is voluntary and by the endower's will, driven by religious motives, as it seeks proximity to Allah Almighty.
Keywords: endower; obligations; voluntary; religious